Pattern of Drug Abuse among Patients in Some Selected Addiction Rehabilitation Centers in Dhaka City - Riya, Sayeda; Rahman, Mahfuzar; Sadeque, Md Zafor; Kabir, Asma; Umar, Badar Uddin (Faridpur Medical College Journal, 2014)
This study was done to find the pattern of drug abuse and its associated factors among the patients admitted in addiction rehabilitation centers. This descriptive cross sectional study was conducted among 150 drug addicted patients at the central drug addiction cure center at Tejgaon, Dhaka. Data were collected with a pre tested structured questionnaire. The study was conducted under the department of community medicine, National Institute of Preventive and Social Medicine (NIPSOM), Mohakhali, Dhaka during March to May 2008. Among the 150 respondents, males constituted 87%, females 12.7%. Most of the respondents (49.3%) were in the age group twenty five to thirty five years. Ninety two percent (92%) of respondents were Muslims, 78.62% urban dwellers, 14.0% from rural areas and 7.33% came from nearby slums. Literacy rate of drug abusers was 81.3%. 33.3% were unemployed, mean family monthly income was ten thousand taka. Drug of initiation was ganja/cannabis in 48.0% and finally addicted to heroin. Inhalation was the route of choice (56.6%), oral route 30.9% and intravenous drug users (IDU's) 12.5% were remarkable. Peer pressure was a major contributing factor 55.5% for drug initiation. Black market (illegal spot) 77.3% was mainly the source of procurement of drug. Mean duration of drug intake was 4.2 years. Significant association was found between male sex and drug intake (p<0.05), and between age group 25-35 years and drug intake (P< 0.05). Drug dependence is highly prevalent among educated people. Familial confliction and peer pressure lead to different drug abuse. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20371 Faridpur Med. Coll. J. 2013;8(2): 63-66